Measuring Customer Orientation Of Salespeople: A Study On Housebuyers - Bakar, Zarir Abu (1999)
This study examines the perception of customer orientation of salespeople among housebuyers. Buying a house is a very complex task involves financial risk to the buyer, thus, the primary objective of this study is to assess the degree which housebuyers rate salespeople as being customer oriented and examining. The relationship between customer orientation and buyer satisfaction. Four dimensions used to measure customer orientation include; responsiveness, ability to fulfil buyer's needs, assistance to buyers on purchase and after sales service. These four dimensions of customer orientation were measured upon 82 research respondents. Statistical tests and analysis were conducted to observe differences, if any, between respondent belonging to variety of socio-economic and demographic characteristics.